Going in thinking process, coming out transformed: Reflections and recommendations from a qualitative research course. Issue 1 (2020) - Mitchell, Donald; Byron, Elizabeth T.; Cross, Jeffrey B.; Oleka, O.J.; Van Eps, Stephanie N.; Clark, Phyllis L.; Sajko, Natalie S.
Abstract: This article presents reflections and suggestions of an instructor and students from a doctoral-level qualitative research course. Given qualitative research courses often lack guidance for best practices and the well-being of doctoral students learning qualitative research is often overlooked, the purpose of this article is threefold: 1) to provide an introductory skeleton for designing a qualitative research course that is structured for classmates to interview each other throughout the semester, what the authors call a student-as-researcher-and-participant design; 2) to provide student reflections from the course; and finally, 3) to offer recommendations for using a student-as-researcher-and-participant design for a qualitative research course.